Children Protection and the Problems, A Book Review “Rencana Aksi Nasional Perlindungan Anak 2015-2019”, Dr. Sofyan A. Djalil SH MA MALD, Kementerian Perencanaan Pembangunan Nasional /Badan Perencanaan Pembangunan Nasional (BAPPENAS) Jakarta, 52 pages - Graha, Alleandria La (Universitas Negeri Semarang, 2021)
Various child protection problems such as increased incident reporting violence against children, cases of children dealing with the law, are increasing the number of children entrusted by their parents at a nursing home, basic services such as education and health has not yet been fully enjoyed by children with disabilities Likewise with children who live in geographically remote areas, that is a challenge the importance of preparing a reference plan holistic-integrative interventions for all stakeholders.